2015
DOI: 10.1016/j.gene.2015.05.056
|View full text |Cite
|
Sign up to set email alerts
|

A glycosyl hydrolase family 16 gene is responsible for the endogenous production of β-1,3-glucanases within decapod crustaceans

Abstract: To identify the gene responsible for the production of a β-1,3-glucanase (laminarinase) within crustacea, a glycosyl hydrolase family 16 (GHF16) gene was sequenced from the midgut glands of the gecarcinid land crab, Gecarcoidea natalis and the freshwater crayfish, Cherax destructor. An open reading frame of 1098 bp for G. natalis and 1095 bp for C. destructor was sequenced from cDNA. For G. natalis and C. destructor respectively, this encoded putative proteins of 365 and 364 amino acids with molecular masses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…4 β-1,3-Glucanases are widely distributed in various organisms, including bacteria, 5 fungi, 6 plants, 7 and invertebrates. 8 They can be classified into two categories depending on their substrate specificities and catalytic patterns. 9 The first class is the exo-β-1,3-glucanase, which cleaves β-1,3-bonds from the nonreducing end of a substrate and sequentially releases glucose monomers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 β-1,3-Glucanases are widely distributed in various organisms, including bacteria, 5 fungi, 6 plants, 7 and invertebrates. 8 They can be classified into two categories depending on their substrate specificities and catalytic patterns. 9 The first class is the exo-β-1,3-glucanase, which cleaves β-1,3-bonds from the nonreducing end of a substrate and sequentially releases glucose monomers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…β-1,3-Glucanases cleave the β-1,3-bonds in a variety of β-1,3-glucans such as curdlan, pachyman, and laminarin . β-1,3-Glucanases are widely distributed in various organisms, including bacteria, fungi, plants, and invertebrates . They can be classified into two categories depending on their substrate specificities and catalytic patterns .…”
Section: Introductionmentioning
confidence: 99%
“…This residue is possible to form disulfide bonds which are very important for the thermal stability of enzymes. 15 The MKAFGlu1 sequence has a low homology when compared to the conservation region in the GH16 member sequences such as Haliotis tuberculata (GenBank access code No. AFQ98375.1), Homoeocera gigantea (GenBank access code No.…”
Section: Sequencing and Analysis Of Mkaf Glu1 Genementioning
confidence: 99%
“…Multiple alignments of amino acid sequences of endo-1,3-β-glucanase GH16 showed that the most conservative amino acid residue feature was "Glu-xxx-Asp-xxx-xxx-Glu" (in the red box Figure 3). 15,16 The first glutamate residue acts as a nucleophilic residue, while the second glutamate acts as an acid-base catalyst residue. 16 However, the most conserved amino acid residue was not found in MKAFGlu1, so it can be concluded that MKAFGlu1 is a new representation of endo-1,3-β-glucanase GH16.…”
Section: Sequencing and Analysis Of Mkaf Glu1 Genementioning
confidence: 99%
“…Christmas Island red crabs, Gecarcoidea natalis (Pocock 1888) and terrestrial hermit crabs, Coenobita brevimanus (Dana 1852) and Coenobita perlatus (Milne Edwards et al 1837) were collected from the rainforest on Christmas Island, and humanely euthanised. Tissues (midgut gland, muscle and gill), were also taken from G. natalis and preserved in RNA later (ThermoFisher Scientific AM7020) as described by Linton et al (2015).…”
Section: Collection Of Tissues From Animalsmentioning
confidence: 99%